The impact of psychological traits on performance in sequential tournaments: Evidence from a tennis field experiment - Christoph Bühren; Philip J. Steinberg (Philipps-University Marburg, School of Business and Economics, 2017)
In order to analyze if heterogeneity in psychological traits affects individual performance in sequential tournaments, we conducted a tennis field experiment. In the experiment, we also varied the payment schemes (individual, team, competition) to control for moderating effects of different incentives. Team incentives, risk taking, and self-esteem reduced performance whereas a preference towards competition enhanced it. On average, we observe a second mover advantage. However, individuals' psychological traits, such as self-esteem or self-efficacy, can turn a second mover into a first mover advantage. Our results shed new light on the discussion of first vs. second mover advantages and performance under pressure. Study findings have implications for psychological requirements of competitive and team tasks in business settings.
Keywords: C93; D81; Z20; M52; 330; performance under pressure; experiment; psychological traits; second mover advantage; tennis; sequential tournaments